The evaluation of occupational needs in psychiatric patients - pilot study - Urszula Żmudzińska; Aneta Bac; Justyna Szulc (University of Applied Sciences in Tarnow, Poland, 2017)
Introduction: Contemporary European understanding of occupational therapy is based on an individual approach to the person, so it is more apt in defining the purpose of therapeutic intervention. Due to the fact that each person has different occupational problems, it is important to identify them well by conducting interviews, establishing relationships, allowing the person to present their point of view, and to use appropriately tailored therapeutic tools and techniques to achieve the designated goal. The purpose of this paper was to present intervention areas for occupational therapy in people with schizophrenia and to show differences in therapeutic needs of people of the same sex, age and medical condition. Materials and methods: The study group consisted of 5 women aged 50-55 years, suffering from schizophrenia and living in the Social Welfare Home. The study was conducted using two questionnaires: EQ-5 and NHP, which illustrated the quality of life of participants in the study. In addition, each person has participated in therapeutic interview, thanks to which occupational problems were identified. Results: Each of the women examined represented a variety of occupational needs, directly related to their needs and problems, which were most relevant to them at the time of the study. The presented occupational needs referred to several life spheres that has often coincided with their current state of health or well-being. Conclusions: Despite similar age, gender, medical conditions and place of residence, each examined person showed different occupational needs. The therapeutic interview turned out to be the basis for identifying occupational needs.